Muslims of the Heartland: How Syrian Immigrants Made a Home in the American Midwest: (By Edward E. Curtis IV) (American Journal of Islam and Society, 2024)
The American Midwest is not a region typically associated with racial and religious diversity. his is in part because, in popular narratives about the US, urban coastal cities are diverse and small towns in “Middle America” are monolithically white and Christian. When ethnic and religious heterogeneity is acknowledged, it is seen as a new historical development based on mid-twentieth and twenty-first century immigration patterns. Muslims, perceived as quintessential outsiders, are perceived as recent and unwelcome interlopers in the religious fabric of America. Edward E. Curtis IV’s Muslims of the Heartland: How Syrian Immigrants Made a Home in the American Midwest calls our attention to both the inaccuracy of these assumptions, and the factors that contribute to these inaccuracies in the first place. Based on archival research, Curtis weaves together vivid portraits of the deep roots that Arab Muslim immigrants have in the Midwest, dating back to the beginning of the twentieth century. By uncovering these erased narratives of Muslims in the Midwest, Curtis provides readers with a powerful corrective to commonplace assumptions about immigration history in the United States.